2012
DOI: 10.7314/apjcp.2012.13.9.4593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Teaching about Breast Cancer via Mobile or Traditional Learning Methods in Gynecology Residents

Abstract: Introduction: Mobile learning enables users to interact with educational resources while in variable locations. Medical students in residency positions need to assimilate considerable knowledge besides their practical training and we therefore aimed to evaluate the impact of using short message service via cell phone as a learning tool in residents of Obstetrics and Gynecology in our hospital. Methods: We sent short messages including data about breast cancer to the cell phones of 25 residents of gynecology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 4 publications
1
38
0
1
Order By: Relevance
“…Another similar studies found that nearly half of the students reported their main sources of information on breast cancer and BSE was the media (Noroozi et al, 2011;Redhwan et al, 2011). In contrast, Alipour et al (2012) reported using the short message service (SMS) via cell phone had a significantly better effect in improving the knowledge about breast cancer and mention as main sources of information on breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Another similar studies found that nearly half of the students reported their main sources of information on breast cancer and BSE was the media (Noroozi et al, 2011;Redhwan et al, 2011). In contrast, Alipour et al (2012) reported using the short message service (SMS) via cell phone had a significantly better effect in improving the knowledge about breast cancer and mention as main sources of information on breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Alipour et al compared learning effect and learner's satisfaction in paper-based and SMS-based method in doctors practicing as gynecology residents by handling printed material and text messages about breast cancer facts and performing pre-and post tests for both methods. They detected a significantly better effect and higher motivation in the SMS group (Alipour et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…9,10 Information sent via text message can be quickly read by the recipient and does not require the user to access the Internet, log-in to an e-mail account, or download any document; this fast-paced style appeals to medical trainees. Text messaging in medical education can function as both a private or a broad (group) method of communication.…”
Section: Embracing New Opportunities With Texting In Medical Educationmentioning
confidence: 99%
“…[8][9][10] One of the more applicable studies assessed learning in obstetrics and gynecology. 10 Residents received information on breast cancer both via text message (2 or 3 messages per day for 17 days) and through a printed booklet.…”
Section: Experiences With Text Messaging In Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation